A new method for the preparation of transparent Y2O3 nanocrystalline ceramic with an average grain size of 20 nm. (June 2020) - Huang, Zhangyi; Deng, Jirui; Wang, Haomin; Zhang, Yutong; Duan, Junjing; Tang, Zhe; Yang, Yao; He, Duanwei; Qi, Jianqi; Lu, Tiecheng
Abstract: We report a method combining the top-down and bottom-up approaches for the fabrication of nanocrystalline ceramic, which can break down the Y2 O3 nanorods and consolidate the broken nanoparticles to 99.1% relative density. The lab-mad nanorods with a length of about 500 nm and a diameter of about 20 nm, exhibit better compressibility and sinterability than the spherical nanopowders when the compaction pressure exceeds 0.4 GPa and the sintering condition is 5 GPa/500 °C, respectively. The obtained nanocrystalline ceramic shows a maximum transmittance of 81.3% in the infrared region, hardness as high as 10.5 GPa and fracture toughness of 2.21 MPa m 1/2 . Graphical abstract: Image, graphical abstract